Dispersed Urban‐Stormwater Control Improved Stream Water Quality in a Catchment‐Scale Experiment. Issue 12 (7th December 2022) - Walsh, Christopher J.; Imberger, Moss; Burns, Matthew J.; Bos, Darren G.; Fletcher, Tim D.
Abstract: Traditional urban drainage degrades receiving waters. Alternative approaches have potential to protect downstream waters, but widespread adoption requires robust demonstration of their feasibility and effectiveness. We conducted a catchment‐scale experiment over 19 years to assess the effect of dispersed stormwater control measures (SCMs), measured as a reduction in effective imperviousness ( EI ) on stream water quality in six sites on two streams. We compared changes in those sites over 7 years as EI decreased, to changes in the 12 preceding years, and in three reference and two control streams. SCMs reduced phosphorus concentrations and summer temperature to reference levels in dry weather where EI was sufficiently reduced, but effects were smaller with increased antecedent rain. SCMs also reduced nitrogen concentrations which were influenced by septic tank seepage in all sites. SCMs had no effect on suspended solids concentrations, which were lower in urban than in reference streams. SCMs increased electrical conductivity: along with reduced temperature this is evidence of increased contribution of groundwater to baseflows. This experiment strengthens inference that urban stormwater drainage increases contaminant concentrations in streams, and demonstrates that such impacts are reversible and likely preventable. Variation in degree of water quality improvement among experimental sites suggests that achieving reference water quality would require SCMs with large retention capacity intercepting runoff from nearly all impervious surfaces, thus requiring more downslope space and water demand. EI is a useful metric for predicting stream water quality responses to SCMs, allowing better catchment prioritization and SCM design standards for stream protection. Plain Language Summary: The way we drain our cities and towns pollutes and erodes our streams and rivers. Water running off, and heated by, roofs and roads carries damaging particles and chemicals. The stormwater drains and pipes that we build transport the polluted runoff, quickly and untreated, to downstream waters. To test if creek water quality downstream of stormwater drainage can be restored, we conducted an experiment. 100s of rain‐gardens that allow water to soak into surrounding soils and be taken up by plants, and rainwater tanks for harvesting, were installed in two suburban catchments. We compared before and after conditions in creeks downstream of the treatments, with conditions in other degraded urban streams, and in undegraded forested streams. Filtering and harvesting stormwater reduced summer temperatures and reduced concentrations of phosphorus and nitrogen, critical contaminants for healthy streams. The reductions were greatest in dry weather, and after small amounts of rain. To achieve water quality similar to forested streams, we need rain‐gardens and harvesting systems that catch runoff from nearly every roof and road upstream. Achieving that will require reserving space near pipe outlets to streams for final treatment systems, and finding ways to use the excess water generated by roofs and roads. Key Points: A long‐term catchment‐scale experiment strengthens inference that urban stormwater drainage increases stream contaminant concentrations Extensive use of dispersed stormwater control measures can reverse stormwater‐induced degradation of stream water quality Achieving reference stream water quality requires retention, treatment and loss of runoff from nearly all catchment impervious surfaces, with high performance standards